Contribuições para a (re)construção das identidades nas aulas de E/LE no peja: relações interculturais - Ramos, Fabrícia Dorneles (2011)
The present research is a reflection about the role of cultural approach in the teaching of Spanish as a Foreign Language (SFL) with students in the Program of Education for Young Adults in a public school in the city of Rio de Janeiro. This work also aims at the construction of pedagogical practices oriented by a critical and political attitude that contributes to the (re)construction of these student's identities by means interaction among cultures and the questioning of hegemonic identities. When we reflect upon the teaching-learning of SFL and the educational practices that contribute to the construction of the student's identities through intercultural approaches, we must mention governmental policies which guide the teaching of this foreign language in Brazil. To this end we analyze critically the LDB and the PCN, as well as the documents which guide foreign language teaching in the city of Rio de Janeiro. Investigations are based upon the Socioconstructionist Theories of Discourse and Identities. In these fields the works of Moita Lopes (1996, 2003, 2005) are paramount, serving as auxiliaries in the understanding of language as socially constructed discourse, and of its relevance for the development of identities and to a view of discourse as social practice, related to concepts of power, ideology and hegemony (cf. Fairclough, 2001). As for the Intercultural theoretical contribution, the studies of Mendes (2004, 2007), and Byram (2000, 2002) were used for their value to the conceptualization and reflection over interculturalism. Contemporary studies on the constructions of identities were also used (cf. Hall, 2000, 2009 e Silva, 2009). The experience in the classroom intended to deconstruct the monoculturalism still very much present in the school environment. By means of the reading of texts from several cultural realities and the from the contact with the difference we build intercultural pedagogical practices in the classrooms, consequently contributing to the (re)construction of identities: the student's and the teacher's identities.